Anesthesia for Placement of a Paracorporeal Lung Assist Device and Subsequent Heart–Lung Transplantation in a Child with Suprasystemic Pulmonary Hypertension and End-Stage Respiratory Failure. Issue 10 (15th May 2016) - Char, Danton S.; Yarlagadda, Vamsi; Maeda, Katsuhide; Williams, Glyn
Abstract : Pediatric patients with end-stage respiratory failure and pulmonary hypertension traditionally have poor outcomes when bridged with extracorporeal membrane oxygenation to lung or heart–lung transplantation. Therefore, several institutions have attempted paracorporeal lung assist devices as a bridge. However, given the small number of patients, little is known about approaches to anesthetic induction in these hemodynamically unstable patients either before placement of a device or anesthetic induction once a device is in situ. In this case report, we describe our anesthetic experience managing a 13-year-old boy for both paracorporeal lung assist device placement and subsequent heart–lung transplantation.